2021
DOI: 10.1155/2021/4711232
|View full text |Cite|
|
Sign up to set email alerts
|

RNF12 Promotes Glioblastoma Malignant Proliferation via Destructing RB1 and Regulating MAPK Pathway

Abstract: Background. RNF12 has been linked to a variety of biological activities, including the control of the MDM2/P53 pathway, although its additional functions remain unclear. RNF12 was discovered to be a new ubiquitin ligase (E3) for RB1, amongst the most frequently repressed proteins in cancer of human. Method. Cell Counting Kit-8 was used to detect the cell proliferation; coimmunoprecipitation was used to determine that RNF12 interacts with RB1. Xenograft studies were used to verify the results. Result. In vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…29 RNF12, as a member of the ring finger protein family, has been reported to be dysregulated in many malignancies. 12,13,30 RNF12 was reported to be overexpressed in glioblastoma, which was correlated with a poor prognosis. 13 Furthermore, RNF12 was found to interact with and target RB1 for degradation to stimulate the MAPK pathway and promote the malignant proliferation of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 RNF12, as a member of the ring finger protein family, has been reported to be dysregulated in many malignancies. 12,13,30 RNF12 was reported to be overexpressed in glioblastoma, which was correlated with a poor prognosis. 13 Furthermore, RNF12 was found to interact with and target RB1 for degradation to stimulate the MAPK pathway and promote the malignant proliferation of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing research showed that RNF12 was involved in the development of cancer 12 . In glioblastoma, RNF12 was reported to be highly expressed and related to poor prognosis of patients 13 . Meantime, RNF12 interacted with and ubiquitinated RB1 to induce its degradation, which activated the MAPK signalling pathway to promote the proliferation of glioblastoma 13 .…”
Section: Introductionmentioning
confidence: 99%
“…No radiotherapy or chemotherapy was given before tissue collection. The OS was calculated based on the information collected from the date of diagnosis to the date of either death or last follow-up from 2019 to 2021 [ 23 ]. The NBTs were collected from patients with brain trauma.…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h of culture, the cells that invaded the back of the membrane were stained using 0.1% crystal violet, followed by fixation with 4% PFA. Based on the total number of cells counted under the microscopy, the invasive capacity was calculated [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation